The selected elements of teenagers’ eating habits of Nowy Targ county with respect to the prevention of cardiovascular diseases - Zięba, Maria; Dębska, Grażyna; Ławska, Wioletta (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. The way of eating in adolescence determines health of the adults. Mistakes and incorrect eating habits from this period predispose to the formation of cardiovascular diseases related to atherosclerosis in adulthood, as well as to unfavourable influence on psychophysical development. Aim. The goal of the thesis was learning about eating habits of teenagers aged 16–19 and assess their body mass index (BMI) in the context of prevention of cardiovascular disease. Material and methods. A research study based on diagnostic survey was conducted in various types of secondary schools of Nowy Targ county in the first half of 2010. The research tool was an author’s anonymous questionnaire subjected to validation (Alfa de Cronbach test = 0.8781). The measurement of body height and weight were used for BMI assessment. The statistical significance value was p < 0.05.The survey examined 859 teenagers, including 366 boys (42.6%) and 493 girls (57.4%) aged 16–19. Results and conclusions. Nutrition habits of the teenagers do not comply with accepted directives concerning rational eating and consequently may foster the development of atherosclerosis in the following years. The comparative analysis of the way the girls and the boys eat proves that the sex determines some nutrition habits of the age group. The girls tend to limit consumption of products being profound sources of saturated fatty acids and cholesterol (red meat, giblets), simultaneously they increase the consumption of dairy products, fresh vegetables and salads. A discrepancy was noticed between what the teenagers know about healthy eating and how they eat every day. The group surveyed usually had a normal weight (77.5%), 8% of the teenagers of both sexes had overweight, and 9.2% of them, generally girls, had underweight.